Layanan Bimbingan Belajar Sebagai Wadah Penggerak Minat Belajar Peserta Didik Di SDK Waipukang - Inang, Maria Yuliana; P. Lejap, Gracianus Edwin Tue (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
The tutoring service is an activity in the guidance and counseling service that helps students to be able to improve learning difficulties at school. Tutoring service activities have become an important forum for answering all needs related to the learning context of students in general. The basic thing that becomes a benchmark is that the stages carried out must consider the convenience side and present students in receiving services provided by anyone, including counselors. The research method uses descriptive qualitative by using the concept of observation, interviews and documentation. The results of the study show that tutoring service activities have an influence on the students concerned with response and cooperation in terms of learning